Microbial Efficacy of Commercial Application of Cecure® CPC Antimicrobial to Ingesta-Contaminated Pre-Chill Broiler Carcasses - Beers, K.; Rheingans, J.; Chinault, K.; Cook, P.; Smith, B.; Waldroup, A. (International Journal of Poultry Science, 2006)
A series of three 12-week in-plant trials were conducted in three USDA-inspected broiler processing facilities (Plants A, B, and C) to determine the antimicrobial efficacy of Cecure (cetylpyridinium chloride or CPC) as a pre-chill whole carcass spray treatment for continuous on-line reprocessing of poultry. The trials were designed to evaluate the microbial effects of treating inspection-held, `visibly contaminated` carcasses in accordance with USDA guidelines for proposed continuous on-line reprocessing trials. Treatment of this group of carcasses was necessary to determine whether Cecure could be utilized as an integral part of a plant`s on-line reprocessing procedures for carcasses accidentally contaminated with digestive tract contents. During each of the three 12-week trials, carcasses were collected on 20 sampling days. On each sampling day, within each plant, four groups of carcasses (n=10) were collected including visibly clean, inspection-passed carcasses; visibly contaminated, inspection-held carcasses; visibly contaminated carcasses after Cecure treatment; and, visibly contaminated carcasses after traditional off-line reprocessing (manual washing with 20 ppm chlorinated water). All carcasses were microbiologically evaluated for aerobic plate count (APC), Escherichia coli (E. coli), total coliform, incidence and level of Campylobacter, and incidence of Salmonella. Treatment of visibly contaminated carcasses with Cecure, in comparison to the other three groups of carcasses, significantly (P≤0.0001) reduced APC by 2.5 to 3.9 logs, E. coli by 1.6 to 2.9 logs, total coliform by 1.2 to 2.7 logs, and Campylobacter by 0.8 to 2.1 logs. CPC treatment also resulted in significant reductions in the incidence of Campylobacter and Salmonella on pre-chill carcasses. Incidence of both Salmonella and Campylobacter on Cecure-treated pre-chill carcasses never exceeded 9% while incidence of these two organisms was as high as 33.5% for Salmonella and 98.7% for Campylobacter on untreated visibly contaminated control carcasses. The microbial condition of Cecure-treated visibly contaminated carcasses was also significantly improved in comparison to the microbial condition of non-treated, inspection-passed `clean` carcasses and traditional off-line reprocessed carcasses. The data suggest that the use of Cecure as a pre-chill carcass spray treatment provides a viable alternative to labor intensive off-line reprocessing as well as providing all carcasses with significantly reduced overall microbial levels and decreased incidence of at least two potential human pathogens.